A systematic review of cervical artificial disc replacement wear characteristics and durability - Lehman, Ronald; Bevevino, Adam J; Brewer, Devon D; Skelly, Andrea C; Anderson, Paul A (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Clinical questions: (1) What evidence is available from studies of cervical total disc arthroplasty (C-ADR) failure and retrieval regarding durability, wear, and reasons for failure of C-ADR? (2) What evidence is available from experimental models regarding the durability of C-ADR beyond 5 years?Methods: We searched electronic databases to identify published reports of explanted cervical artificial discs and biomechanical simulations of disc wear.Results: Nine articles were identified describing 17 devices explanted from human patients and four articles describing 23 devices explanted from non-human subjects. Wear properties were not consistently reported across studies, so summaries for specific variables are based on few cases. No device had been implanted longer than 4 years. In both human and non-human subjects, devices showed evidence of metallic and polymeric (for discs with polymer components) debris. Inflammatory cells were frequently present in surrounding soft tissues. Signs of infection were uncommon. Four patients had reactions interpreted as hypersensitivity to metal. We identified three articles on biomechanical wear simulations. Devices were tested between 10 and 20 million cycles in axial loading, flexion/extension, and lateral bending. No device failures were reported. One study suggests such simulations may represent 50 or more years of wear in actual patients.Conclusion: Cervical disc implants consistently produced polymeric and metallic debris, which was typically accompanied by inflammation. Hypersensitivity to metal may increase risk for device failure. Biomechanical simulations indicate that cervical disc implants may be durable beyond the currently reported length of clinical follow-up.